A photoluminescent covalent triazine framework: CO2 adsorption, light-driven hydrogen evolution and sensing of nitroaromatics. Issue 35 (12th August 2016) - Bhunia, Asamanjoy; Esquivel, Dolores; Dey, Subarna; Fernández-Terán, Ricardo; Goto, Yasutomo; Inagaki, Shinji; Van Der Voort, Pascal; Janiak, Christoph
Abstract : Porous PCTF-8 has a fluorescence quantum yield of 31% which is quenched by trinitrophenol, and Pt@PCTF-8 yields H2 with visible light. Abstract : A highly photoluminescent (PL) porous covalent triazine-based framework (PCTF-8) is synthesized from tetra(4-cyanophenyl)ethylene by using trifluoromethanesulfonic acid as the catalyst at room temperature. Due to triazine units in the framework, the PCTF-8 exhibits excellent thermal stability (>400 °C). The Brunauer–Emmett–Teller (BET) specific surface area of PCTF-8 is 625 m 2 g −1 which is lower than the one obtained from the synthesis under Lewis acid conditions (ZnCl2 ). At 1 bar and 273 K, the PCTF-8 adsorbs a significant amount of CO2 (56 cm 3 g −1 ) and CH4 (17 cm 3 g −1 ) which is highly comparable to nanoporous 1, 3, 5-triazine frameworks (NOP-1-6, 29–56 cm 3 g −1 ). This nitrogen rich framework exhibits good ideal selectivity (61 : 1 (85% N2 : 15% CO2 ) at 273 K, 1 bar). Thus, it can be used as a promising candidate for potential applications in post-combustion CO2 capture and sequestration technologies. In addition, photoluminescence properties as well as the sensing behaviour towards nitroaromatics have been demonstrated. The fluorescence emission intensity of PCTF-8 is quenched by ca. 71% in the presence of 2, 4, 6-trinitrophenol (TNP). From time-resolved studies, a static quenching behaviour was found. This high photoluminescence property is used for hydrogen evolving organic photocatalysis from water in the presence of a sacrificial electron donor and a cocatalyst.